Naringin Exerts Therapeutic Effects on Mice Colitis: A Study Based on Transcriptomics Combined With Functional Experiments - Jianyi Dong; Yuanyuan Chen; Fang Yang; Weidong Zhang; Kun Wei; Yongjian Xiong; Liang Wang; Zijuan Zhou; Changyi Li; Jingyu Wang; Dapeng Chen (Frontiers Media S.A., 2021)
Naringin has been shown to exert protective effects in an animal model of ulcerative colitis, but detailed mechanisms remain unclear. This study aimed to investigate function and signaling mechanisms underlying naringin-induced therapeutic effects on colitis. Two mouse models were established to mimic human Inflammatory bowel disease (IBD) by treating drinking water with dextran sodium sulphate or intra-colonic administration of 2, 4, 6-trinitrobenzene sulfonic acid. Transcriptomics combined with functional experiments were used to investigate underlying mechanisms. Colitis symptoms, including weight loss and high disease activity index were significantly reversed by naringin. The inflammatory response, oxidative reactions, and epithelial cell apoptosis that occur with colitis were also alleviated by naringin. After naringin treatment, transcriptomics results identified 753 differentially expressed mRNAs that were enriched in signaling pathways, including the neuroactive ligand-receptor interaction, calcium signaling, and peroxisome proliferator-activated receptor (PPAR) signaling. The naringin-induced alleviation of colitis was significantly inhibited by the PPAR-γ inhibitor BADGE. In IEC-6 and RAW264.7 cells incubated with lipopolysaccharide (LPS), NF-κB-p65, a downstream protein of PPAR-γ, was significantly increased. Naringin suppressed LPS-induced high expression of NF-κB-p65, which was inhibited by small interfering RNA targeting PPAR-γ. Our study clarifies detailed mechanisms underlying naringin-induced therapeutic effects on mice colitis, and PPAR-γ was found to be the main target of naringin by functional experiments both in vivo and in vitro. Our study supplies new scientific information for the use of naringin in colitis treatment.